Numerical analysis of wake wash reduction for catamaran with hydrofoils. (June 2023) - Terui, Chota; Hino, Takanori; Takagi, Youhei
Abstract: Catamarans are popular for fast sea transportation because of their high potential of speed and stability. However, the wake wash generated by catamarans often interfere surrounding environment. For the prevention of large waves generated by catamarans, a stern hydrofoil is known to be one of the effective devices. In the present study, the effect of hydrofoil attached at the stern of a catamaran for the wake wash reduction is investigated using CFD. The various configurations of a stern hydrofoil are designed and their performance are examined with respect to resistance in calm water and wave amplitudes. The computational domain is taken large enough to be able to analyze the wave field far downstream. In addition to the bare hull and the hull with foil cases, the bare hull cases with the attitudes fixed to those of the cases with the foil are simulated for the detailed analysis of foil effects. The inter-comparison of these cases makes it possible to separate the foil effects into the hull attitude change effect and the foil-generated wave effect. The wake wash reduction by stern foil system is achieved with the appropriate combination of hull attitude change and the interaction of hull waves and foil waves. Finally the design directions of a stern hydrofoil for the wake wash reduction are suggested.